Immediate effects of muscle energy technique on pain and range of motion in patients with chronic non-specific neck pain: A randomized controlled trial - Hussain, Ghulam; Arsh, Aatik; Rehman, Fazal; Khan, Shumaila (Pakistan journal of medical sciences, 2025)
Objective: To determine the immediate effects of muscle energy technique and conventional physical therapy compared to conventional physical therapy alone on pain and range of motion (ROM) in patients with chronic mechanical neck pain. Methods: A randomized controlled trial (RCT) was conducted at Physical Therapy Department Hayatabad Medical Complex Peshawar from March 2022 to August 2022. A total of 50 subjects, aged 18 to 50 years with non-specific neck pain for ≥ 3 months were included. Participants were randomly assigned to two groups through lottery approach. Participants in experimental group (n=25) received muscle energy technique along with conventional physical therapy while participants in control group (n=25) received conventional physical therapy. Baseline and post-intervention (immediately after the session) neck pain intensity and neck ranges were measured by Numeric Pain Rating Scale and goniometer respectively. Results: Mean age of participants was 32.30 ± 7.75. Of the 50 participants, 36 (72%) were male while the remaining 14 (28%) participants were female. At baseline, there were no significant differences (P>0.05) between experimental and control groups. However, at post-intervention, there were significant differences in pain intensity (p=0.024), cervical flexion (p<0.001), extension (p=0.003), left rotation (p<0.001), right rotation (p<0.001), left lateral flexion (p=0.027) and right lateral flexion (p<0.001) ROMs between experimental and control groups. Conclusion: Muscle energy technique along with conventional physical therapy is more effective in decreasing neck pain and improving cervical ROM compared to conventional physical therapy alone in individuals with chronic mechanical neck pain. Trial Registration: Iranian Registry of Clinical Trials (Reference No.: IRCT20220209053976N1). doi: https://doi.org/10.12669/pjms.41.5.9601 How to cite this: Hussain G, Arsh A, Rehman F, Khan S. Immediate effects of muscle energy technique on pain and range of motion in patients with chronic non-specific neck pain: A randomized controlled trial. Pak J Med Sci. 2025;41(5):1365-1369.  doi: https://doi.org/10.12669/pjms.41.5.9601 This is an Open Access article distributed under the terms of the Creative Commons Attribution License (http://creativecommons.org/licenses/by/3.0), which permits unrestricted use, distribution, and reproduction in any medium, provided the original work is properly cited.